Epidemiological Analysis of Outcomes of Small Obstetric Operations - I. V. Taranenko; A. V. Lubimova (Эпидемиология и вакцинопрофилактика, 2020)
Relevance Тhe Priorities in the field of the state demographic policy of our country are to improve the reproductive health of the population, improve the system of obstetric care and the quality of medical care. An urgent problem is the quality of life of women in the postpartum period after injuries of the soft tissues of the birth canal and the use of obstetric in natural delivery (episiotomy, vacuum extraction of the fetus, the imposition of obstetric forceps, manual placental separation and manual examination of the uterine cavity). High rates of non-communicable complications confirm the need for further study of long-term effects and ways to improve the quality of care for women in the postpartum period. There is insufficient information on the dynamics of health indicators in the postpartum period, on the relationship of violations with various socio-hygienic, behavioral, medical and organizational factors acting in relation to the woman in this period. Obstetric operations and soft tissue injuries of the birth canal are also a risk factor for the development of purulent-septic infections in the postpartum period. For a comprehensive analysis of the factors determining reproductive behavior in women during rehabilitation, it is necessary to assess the effectiveness of measures in the postpartum period, the risks of long-term consequences for women after small obstetric operations. Aims. Summarize the available literary data and present modern views on the problem of the quality of life of women in the postpartum period after obstetric operations with natural delivery. Materials and methods. Analysis of publications on the quality of life in the postpartum period in the databases PUBMED, E-Library, Google Scholar, etc. from 2013 to 2019. The study includes sources in Russian and English, containing information on the frequency of various obstetric benefits for natural delivery, infectious and non-infectious complications after their implementation. Results. Birth canal Injuries (ruptures of the cervix, vaginal walls, perineum and vulva) account for up to 40% of cases [1,2]. Noted that in nulliparous they occur in 73%, while the performance of obstetric benefits (episiotomy, forceps, vacuum extraction) reach 90%. The frequency of perineal ruptures of the III degree ranges from 0.4 to 5% [3]. The frequency of ruptures of the perineum I-II degree does not have an official form of accounting and registration, also refers to injuries of the birth canal. According to official statistics, the frequency of application of vacuum extraction of the fetus in the European countries ranges from 2.8% to 16.7% of the total number of births, and in our country according to the Department of monitoring, analysis and strategic development of health, Ministry of health of the Russian Federation, the frequency of execution of vacumm extraction of the fetus and the imposition of obstetric forceps is the 11.04 and 0.56 per 1000 births. The number of women who have had these situations in childbirth is very high. At this stage, epidemiological monitoring of the postpartum period of women is reduced to monitoring infections in the field of surgery and predictors of the development of the infectious process. However, given the multifactorial nature of the problem, monitoring the quality of life in the postpartum period after these operations remains without due attention. First of all, they note negative changes after obstetric operations, such as a feeling of pain when walking, sitting, lifting weights. Unpleasant sensations in the sutures remain in the postpartum period for 2–3 weeks after discharge. After 3–4 weeks, the feeling of pain is replaced by itching and burning, which also gives discomfort to the woman. The situation is complicated by the lack of women's psychological support in this matter from the doctor. Many patients are afraid to address and ask questions about personal feelings and sexual life at the reception. Sexual dysfunction may be formed after performing obstetric benefits or injuries to the soft tissues of the birth canal, actually should be regarded as maternal morbidity. The introduction of epidemiological surveillance of the psychophysiological state of women after small obstetric operations will allow timely work with patients about the features of the postpartum period, to increase the percentage of satisfaction with the quality of services provided in obstetric institutions. The study of risk factors for the development of non-infectious diseases in women after childbirth allows us to calculate the degree of effectiveness of the planned medical and social measures for the prevention of negative consequences. Conclusions: The Development and implementation of epidemiological surveillance of women who have received obstetric benefits or had soft tissue injuries of the birth canal will allow to form an understanding of the rules and tactics of postpartum management, as well as to improve the quality of life of women during rehabilitation.